-6=11x-5x

Simple and best practice solution for -6=11x-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=11x-5x equation:


Simplifying
-6 = 11x + -5x

Combine like terms: 11x + -5x = 6x
-6 = 6x

Solving
-6 = 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-6 + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
-6 + -6x = 0

Add '6' to each side of the equation.
-6 + 6 + -6x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -6x = 0 + 6
-6x = 0 + 6

Combine like terms: 0 + 6 = 6
-6x = 6

Divide each side by '-6'.
x = -1

Simplifying
x = -1

See similar equations:

| 5x+2(6)=3x(11) | | 15=5-2x | | 6(2x+7)=126 | | -4(-2+5x)=28 | | X^2+4xy+5x=0 | | (-3)/(-10)*0*(-2)= | | -5(7+7x)=-105 | | 3x+12-4x=20 | | 8x+7=x-1 | | -4(-7+6x)=-236 | | x^2+-20x+39=0 | | d^2+8c+12=0 | | -4+4x=2x+14 | | 6x+6=-2+7x | | 5x^2-22=0 | | 2x-7=7x-32 | | 15.4c-13.7=14x-17.2 | | -4+7X=-2x-94 | | 6x+6=-4x+6 | | 4(3+2x)-7= | | (-21)/3-5*(-5)= | | 4y+16x=20 | | .75(x+2)-(2/3)(x-3)=2 | | 4x-115=95-11x | | 3y=9x-3 | | 6x+10=x+60 | | (2d+1)/3=6 | | 167x+12=1478 | | 3x+7=7x+7 | | -7s-5-7s+9= | | 2y=4x-24 | | x^2-23x+46=0 |

Equations solver categories